A Novel Thermostable GH3 β-Glucosidase from Talaromyce leycettanus with Broad Substrate Specificity and Significant Soybean Isoflavone Glycosides-Hydrolyzing Capability. (23rd October 2018) - Li, Xinxin; Xia, Wei; Bai, Yingguo; Ma, Rui; Yang, Hong; Luo, Huiying; Shi, Pengjun
Abstract : A novel β -glucosidase gene ( Bgl3B ) of glycoside hydrolase (GH) family 3 was cloned from the thermophilic fungus Talaromyce leycettanus JM12802 and successfully expressed in Pichia pastoris . The deduced Bgl3B contains 860 amino acid residues with a calculated molecular mass of 91.2 kDa. The purified recombinant Bgl3B exhibited maximum activities at pH 4.5 and 65°C and remained stable at temperatures up to 60°C and pH 3.0−9.0, respectively. The enzyme exhibited broad substrate specificities, showing β -glucosidase, glucanase, cellobiase, xylanase, and isoflavone glycoside hydrolase activities, and its activities were stimulated by short-chain alcohols. The catalytic efficiencies of Bgl3B were 693 and 104/mM/s towards p NPG and cellobiose, respectively. Moreover, Bgl3B was highly effective in converting isoflavone glycosides to aglycones at 37°C within 10 min, with the hydrolysis rates of 95.1%, 76.0%, and 75.3% for daidzin, genistin, and glycitin, respectively. These superior properties make Bgl3B potential for applications in the food, animal feed, and biofuel industries.